Nutritional Status of Children on Complementary Feeding Practices - Jadav, N. B.; Kumari, Mamta; Singh, Jagdeep (Indian Journal of Extension Education, 2021)
Complementary feeding is transitional phase where the infant is introduced with the solidÂ foods. It is a gradual change from breastfeeding to family foods to the baby achieving six months of age. Introduction of timely, adequate and balanced weaning food is perhaps oneÂ of the most important measures to combat infantâ€™s malnutrition. Poor feeding practices results in poor performance in later life. For the study, 25 children were selected from anÂ Anganwadi Centre and discovered the prevalence of malnutrition among the children (1-5 years) on the basis of height, weight, head/chest circumference, MUAC, etc. The degree of malnutrition was higher in boys than girls due to poor socio-economic conditions, lack ofÂ knowledge of mothers, dietary pattern, early marriages, lack of weaning/supplementary food, etc. To prevent childhood malnutrition motherâ€™s knowledge and good feeding practices should be prioritized. Thus, promotion of appropriate feeding practices should focus notÂ only to mothers but also on other family members through Anganwadi Workers to prevent malnutrition.